2010
DOI: 10.1021/jp105883p
|View full text |Cite
|
Sign up to set email alerts
|

3D Nanoscale Characterization of Thin-Film Organic Photovoltaic Device Structures via Spectroscopic Contrast in the TEM 1

Abstract: The three-dimensional characterization of third generation photovoltaic device structures at the nanometer scale is essential to the development of efficient, reliable, and inexpensive solar cell technologies. Electron tomography is a powerful method for three-dimensional characterization; however, the application of this method to the organic materials systems that comprise typical high-efficiency devices is complicated by the difficulty in generating contrast from the compositionally similar materials. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
147
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 33 publications
9
147
0
Order By: Relevance
“…The high contrast of the plasmon-loss image enables a 3D electron tomography reconstruction of the P3HT-PCBM thin-film as first reported by Herzing et al 7 However, the plasmon intensity follows a non-linear relationship with respect to specimen thickness (t) and is therefore not a valid signal for electron tomography. The probability for n plasmon scattering events P n is given by Poisson statistics as (1/n!…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…The high contrast of the plasmon-loss image enables a 3D electron tomography reconstruction of the P3HT-PCBM thin-film as first reported by Herzing et al 7 However, the plasmon intensity follows a non-linear relationship with respect to specimen thickness (t) and is therefore not a valid signal for electron tomography. The probability for n plasmon scattering events P n is given by Poisson statistics as (1/n!…”
mentioning
confidence: 95%
“…Herzing et al 7 have shown that for poly(3-hexylthiophene) (P3HT)-phenyl-C61-butyric acid methyl ester (PCBM) bulk heterojunction solar cells the contrast can be improved by imaging with electrons that have lost energy to the material via plasmon excitations. The plasmon-loss images at different specimen tilts were used to reconstruct the 3D volume as in a conventional tomography experiment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Energy filtered TEM (EFTEM) is an increasingly common method for enhancing contrast in organic materials. This is accomplished by introducing a post-specimen energy window that only allows electrons having a specific range of energies form the image [4][5][6][7][8][9][10][11]. The motivation behind the use of this technique is that the different materials within the bulk heterojunction (BHJ) have plasmon losses at different energies.…”
Section: Introductionmentioning
confidence: 99%